Preliminary observations of the reproductive biology of the Frenchman seabream Polysteganus baissaci (Sparidae) from Mauritius. Issue 4 (17th December 2019) - Caussy, L; Appadoo, C; Sauer, WHH; Potts, WM
Abstract : The Frenchman seabream Polysteganus baissaci is an important commercial fish species found on the slopes of the fishing banks of the exclusive economic zone of Mauritius. Exploitation of this species started in 2007, and it is targeted using hydraulic reels with baited hooks. The introduction of suitable management measures is important for this fishery and a sound understanding of the biology is required. Monthly biological data were collected over a 2-year period from fish landed in the commercial catch, to investigate aspects of the biology. A total of 698 females and 1 129 males (sex ratio 1:1.6) were collected from commercial fishing vessels operating on the Nazareth Bank. Females dominated smaller size classes (30–36 cm total length [TL]), whereas males were mostly present at larger sizes (37–44 cm TL). Although ripe and spent female gonads were found throughout the study period, the gonadosomatic index (GSI) revealed a peak in spawning between April and September, coinciding with the cooler sea temperatures in the region. Male GSI (0.169 [SD 0.0443]) during its peak month (August) was more than 14-times lower than the female GSI (2.470 [SD 1.0185]) during its peak month (July), and this, together with male and female length frequencies and adult sex ratios, provides strong supporting evidence for protogyny in this species. Although this fishery appears to harvest adults exclusively, which is positive in terms of sustainability, the potential hermaphroditism in this species necessitates implementation of a conservative harvest strategy, including effort limitation and a closed fishing season over the peak spawning period.